Differences in Learning Outcomes and Critical Thinking Skills of Students Taught Using Powtoon Media and Ispring Presenter with A Problem-Based Learning Model on Reaction Rate Material - John Hebert Siallagan; Ratna Sari Dewi (Universitas Lampung, 2025)
This study aims to determine the differences in learning outcomes and critical thinking skills of students taught using powtoon media and ispring presenter with a problem-based learning model on reaction rate material. This study used two research samples selected by purposive sampling at SMA negeri 4 Medan and each numbered 36 students. The research design used in this study was the pretest posttest control group design, which involved the experimental class I and the experimental class II. The result of the study indicate that the difference in learning outcomes between students taught using powtoon and ispring presenter media with the problem based learning yielded a sig.(2-tailed) value of 0.044 this means there is a difference in student learning outcomes taught using powtoon media and ispring presenter media with the problem based learning model, where the increase in learning outcomes using powtoon of 0.74 and using ispring presenter of 0,64. In the difference in critical thinking skills of students taught using powtoon and ispring presenter media with the problem based learning model sig.(2-tailed) was 0.046 this means there is a difference in the critical thinking skills of student taught using powtoon and ispring presenter media with problem based learning model